A Model for Academic Planning - Jones, Larry R. (Canadian Journal of Higher Education, 1978)
Under conditions of limited and selective growth, institutions propose resource allocation changes which are not strictly related to overall institutional enrollment levels. These proposals often focus attention on the resource impact of internal shifts in student demand and the desirability of maintaining minimum or "critical mass "levels of academic program breadth and quality. This paper addresses the academic planning procedures needed to advance non-enrollment driven resource maintenance and acquisition proposals at institutional and state levels. The purpose of critical mass modeling for academic planning is to facilitate analysis, prioritization and negotiation of academic program alternatives and resources. The critical mass approach to academic planning would establish a campus-wide process and informa- tion base for prioritization of academic program development through (a) analysis of existing breadth and depth of faculty expertise in instruction and research at the sub- disciplinary level, (b) identification of subdisciplinary areas in which academic units would like to provide instruction and research in the future. Critical mass denotes the level of course offerings and research which academic units could not reduce and still maintain programs which fulfill their own objectives compatible with the overall mission of their institution. Critical mass program size and "core" resource requirements would be established by academic unit faculty and then would be negotiated with committees of academic senates and with institutional administrations. The planning process described is designed for application in medium and large sized institutions in which formal, comprehensive and integrated academic ¡resource planning systems do not operate presently.